Effect of nucleotides and turmeric extract on blood protein and body weight of broiler kept in open cages. Issue 1 (1st March 2022) - Tugiyanti, E; Susanti, E; Ismoyowati, I; Rosidi, R
Abstract: Indonesia's wet tropical climate is a condition that does not support the development chickens. Therefore, this study aims to analyze the effect of nucleotides and turmeric extract in basal feed on broilers' blood protein and body weight. Data was collected using a Completely Randomized Design (CRD) with 7 treatments that comprised of negative and positive control. Meanwhile, the negative aspects include basal feed + plus Zink Bactitracin 0.1 g, while the positive control consists of N0K1, N1K0, N1K1, N2K0, and N2K1. The results showed that nucleotide supplementation and turmeric extract in the feed had no significant effect on blood PCV, TPP, albumin levels, and broiler body weights. Furthermore, blood protein increases due to the high levels of nucleotides and turmeric extract. The 5 g of nucleotide supplementation and turmeric extract produce the same broilers blood protein and body weight.